FRI0577-HPR Work ability in patients with early rheumatoid arthritis; emphasis on mechanical exposure and shoulder function. (23rd January 2014) - Bilberg, A.; Bremell, T.; Balogh, I.; Mannerkorpi, K.
Abstract : Background: Work disability in Rheumatoid Arthritis (RA) usually occurs soon after disease onset and often prevails during the disease course. Associated factors such as physical functioning and work-related mechanical exposure have been sparsely investigated in early RA. Objectives: A cross-sectional study was conducted to investigate work ability and associated factors in patients with early RA, with emphasis on work-related mechanical exposure, shoulder function and activity limitations related to the shoulder-arm-hand. Methods: One hundred and thirty-five patients, 103 women and 32 men, with early rheumatoid arthritis were recruited from three rheumatology units in the West region of Sweden. The mean age for the study population was 48 (SD 9.60) years, the mean disease duration 21 (SD 9.6) months and the mean DAS28 score 3.7 (SD1.37). Measurements: Work-related mechanical exposure was assessed with the Mechanical Exposure Index (MEI). Physical work load was assessed by dividing patients into 5 occupational categories based on most recent type of work. Shoulder function was assessed by isometric shoulder strength, active shoulder-arm movement, and activity-induced shoulder pain. Hand-grip force was also recorded. Activity limitations related to the upper extremities were assessed with the Disability of the Arm, Shoulder and Hand (DASH) questionnaire, and disease activity by the DAS28 score. Statistics: The mean, standard deviations and percentages are presented. The Spearman´s correlation coefficient was used to analyse the associations between work hours and other assessments. Results: The majority of patients, 76.5% were working full or part-time. Work hourswere found to correlate negatively with work-related mechanical exposure (MEI) (rs-0.34, p< 0.001), and positively with physical work load (rs 0.26, p= 0.003). Considering shoulder function, work hours were found to correlate positively with shoulder-arm movement (rs 0.33, p< 0.001), and shoulder strength (rs 0.25, p= 0.004) and correlate negatively with activity induced shoulder pain (rs -0.45 p < 0.001). Significant correlations were also found between work hours and hand grip force (rs 0.45, p< 0.001), activity limitations (DASH) (rs -0.61, p < 0.001) and the DAS28 score (rs -0.43, p< 0.001). Conclusions: Work ability in early rheumatoid arthritis is associated with work-related mechanical exposure, shoulder function and activity limitations related to the shoulder-arm-hand. Attention should be directed towards these factors as well as to the inflammatory activity. Disclosure of Interest: None Declared